The Control of an Industrial Manipulator's Positioning System Using Dahlin Algorithm. (2015) - Clitan, Iulia; Abrudean, Mihail; Muresan, Vlad
Abstract: This paper presents the design of a digital controller for the horizontal positioning movement of an industrial manipulator. The manipulator represents an hydraulically driven unloading machine that extracts the billets from a rotary hearth furnace. The positioning movement is approximated by a second-order process with time delay. The Dahlin algorithm is applied since it generates acceptable results in terms of performances. The algorithm specifies that the closed-loop performance of the process behave similarly to a continuous first-order process with time delay. The time constant of the closed-loop system serves as a tuning parameter for the control algorithm and different controllers are derived. The obtained controllers are compared via simulation based on the basis of overall performances and ringing behavior.